(untitled) (Research, Society and Development, 2022)
Medals are one of the symbols that best represent success in sport. Numerous studies, especially in the context of the Olympic Games, have used the ranking of medals won by a country to investigate social and economic determinants that may be related to success. The objective of this work was to analyze the social and economic determinants of success in Brazilian School Games (JE) in the period from 2007 to 2015. The research carried out an estimation by means of a fixed-effect panel data regression, encompassing all Brazilian federative units (UF) participating in the School Games from 2007 to 2015. The dependent variable was the total number of medals won in the period. According to the results, the most significant determinants were population, homicide rate, Basic Education Development Index (IDEB) score, Union complementation to the National Fund for Development of Basic Education (FUNDEB) and host state.